The Effect of Product Quality and Promotion on the Purchase Decision of T-Shirt Distro Reject Official Store Sukabumi - Nugraha, Bayu Aji; Gunawan, Rachmat; Yulianingsih (MultiTech Publisher, 2024)
This study aims to determine and identify product quality and promotion either simultaneously or partially on the decision to purchase T-Shirt Distro Reject Official Store Sukabumi. Sampling amounted to 100 respondents who were taken by purposive sampling technique, namely the technique of determining the sample with certain considerations. The questionnaire was tested with validity test, reliability test, and classical assumption test. The results of these tests are valid, reliable, and can be used for regression data. The analytical method used in this research is descriptive and verification with a quantitative approach. The results showed that the variables of product quality and promotion either simultaneously or partially had a positive and significant effect on purchasing decisions for T-Shirt Distro Reject Official Store Sukabumi. The result of testing the coefficient of determination R (square) is 55.1%, while the rest is 49.9%. The relationship between product quality and promotion is strong in the same direction as the correlation coefficient of 0.743.